POPULASI DAN KARAKTERISTIK MORFOLOGI MERANTI (Shorea montigena, Slooten) DI KECAMATAN INAMOSOL, KABUPATEN SERAM BAGIAN BARAT - Johan M Matinahoru (JURNAL HUTAN PULAU-PULAU KECIL, 2023)
In Indonesia, there are approximately 506 species of meranti, which are spread across Sumatera, Kalimantan and Maluku. The population of meranti in Maluku is found on the islands of Taliabu, Mangole, Sanana, Buru and Seram. These islands, which are located in the easternmost part of Indonesia, are Seram Island. The distribution of meranti on Seram Island is found in West Seram District (Inamosol Sub District) and Central Maluku District (Tehoru Sub District). The purpose of this study was to determine the potential population, morphological characteristics and distribution patterns of meranti. The results showed that the potential population of meranti per hectare found in the natural forest of Inamosol Sub District was at the tree level of 14.2 stems, poles 19.4 stems, sapling 41 stems, and seedlings 242 stems. In general, the morphological characteristics of meranti found were oval leaf shape, semi-circular but tapered leaf tip shape (cuspidate), rounded leaf base, straight tree trunk, cylindrical and brown mixed with a few black spots, flower crowns. pale pink, stamens 12-15, fruit brown color, oval breech (obovate), three-winged with red color, fruit wing length 8-11cm, fruit wingspan 2-3 cm, fruit diameter approximately 1 cm. Based on the morphological characteristics of natural meranti stands in Inamosol Sub District were categorized into red meranti group with the species of Shorea montigena Slooten. The distribution of meranti stands naturally found is in group pattern.